Measuring the fiscal and equity impact of tax evasion: evidence from Denmark and Estonia - Salvador Barrios; Bent Greve; M. Azhar Hussain; Alari Paulus; Fidel Picos; Sara Riscado (European Commission, Joint Research Centre (JRC), 2017)
In the European context where fiscal consolidation is required in many countries, tax non-compliance behaviour becomes a very relevant issue for governments and policy makers. In this paper, we aim at contributing to the assessment of tax non-compliance, by estimating individual measures of tax evasion, focusing on employment earnings for two countries, Denmark and Estonia. Additionally, we simulate two different scenarios - a "true world" where some individuals underreport their income to the tax authorities and a "perfect world" where everyone reports truthfully their incomes - in the European microsimulation model EUROMOD, allowing us to obtain the fiscal and distributional effects of taking into account evaded employment income. Furthermore, the Estonian country case allows us to illustrate the importance of linking survey and administrative data not only to accurately estimate tax evasion, but also to correct survey income amounts for measurement error. Preliminary findings indicate that taking into account non-reported incomes has non-negligible fiscal and distributional effects when these are taken into account to compute tax liabilities and benefits, even in a country where estimated non-reported income represent a low percentage of earnings, such as Denmark.
Keywords: 330; Tax evasion; microsimulation